Manunggal Daya Village: Building Independence Through Economic and Cultural Empowerment - Kezia Arum Sary; Muhammad Saudi Firdaus; Ani Lathifatunisa; Siti Nor Aleyda; Irma Adelina Panjaitan; Rico Ariefudin; Muhammad Ansarullah; Hadie Pratama Tulili; Sintanur Agustina; Lims Giyofanni; Rima Octavianur; Regita Regita (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
This research aims to identify and analyze the potential of the Manunggal Daya Village community. The methods used are interviews, observation, concept preparation, and implementation process. Interviews were conducted with community leaders, local entrepreneurs, and farmers to obtain comprehensive information on existing potentials, totaling three people. Observations are carried out to understand real conditions in the field, such as educational facilities, agricultural practices and health services. From the results of this research, a video profile was created that displays these potentials, as an educational and promotional medium to attract the attention of parties interested in village development. The process of making a video profile of the potential of Manunggal Daya Village begins with preparing a thorough concept. This includes several interrelated strategic steps to ensure that the resulting video is able to convey the message in an effective and interesting way.  The findings obtained show that there is potential for the residents of Manunggal Daya Village in the fields of agriculture, economics, education and health. However, several challenges such as lack of facilities and facilities hinder the development of this potential. It is hoped that this research can become a reference for village development policies and improve the quality of life of the community.Pembuatan Video ini bertujuan untuk mengidentifikasi dan menganalisis potensi masyarakat Desa Manunggal Daya. Metode yang digunakan adalah wawancara, observasi, penyusunan konsep, dan proses pelaksanaan. Wawancara dilakukan dengan tokoh masyarakat, pengusaha lokal, dan petani untuk mendapatkan informasi yang komprehensif mengenai potensi yang ada yang berjumlah tiga orang. Observasi dilakukan untuk memahami kondisi nyata di lapangan, seperti sarana pendidikan, praktik pertanian, dan layanan kesehatan. Dari hasil perancangan ini, dibuatlah video profil yang menampilkan potensi-potensi tersebut, sebagai media edukasi dan promosi untuk menarik perhatian pihak-pihak yang berkepentingan dalam pengembangan desa. Proses pembuatan video profil potensi Desa Manunggal Daya dimulai dengan penyusunan konsep yang matang. Hal ini mencakup beberapa langkah strategis yang saling berkaitan untuk memastikan bahwa video yang dihasilkan mampu menyampaikan pesan dengan cara yang efektif dan menarik.  Adapun temuan yang didapatkan menunjukkan adanya potensi warga Desa Manunggal Daya dalam bidang pertanian, ekonomi, pendidikan, dan kesehatan. Namun, beberapa tantangan seperti kurangnya sarana dan fasilitas menghambat perkembangan potensi tersebut. Pembuatan video ini diharapkan dapat menjadi referensi bagi kebijakan pembangunan desa dan peningkatan kualitas hidup masyarakat.